SISTEM MONITORING VOLUME AIR MENGGUNAKAN SENSOR ULTRASONIK DAN MONITORING OUTPUT VOLUME AIR MENGGUNAKAN FLOW METER BERBASIS ARDUINO - Br Pelawi, Servinta Damayanti; Manan, Saiful (Gema Teknologi, 2017)
Servinta Damayanti Br Pelawi,Saiful Manan, in this paper explain that method of realization of making purification and monitoring volume of water, purification of water using small molecules such as sand, charcoal, cotton, etc. and monitoring the volume of water using the HC-SR04 ultrasonic sensor. where this ultrasonic sensor will detect the water inside the sensor distance sensor to objects that is 2cm and 25cm. When the water has reached the limit of 2cm and 15cm then the buzzer will light up giving a warning. and will display on the HMI in the form of cm, to run the pump we click the start button at hmi the pump will turn on and the water inside the reservoir will enter reverse osmosis, Ro will process water, clean water will be read by the flow meter, flow meter will detect incoming water and will display the results in the HMI in the form liter, and Arduino UNO is used as a control system for HMI output input signals, sensors, flow meters, and buzzers.